Language and Gender Inequality: Proverbs that Debase Women in Igbo Land and their Interpretations - Ifeanyi M. NWOKEOCHA (Citakonsultindo, 2023)
Gender inequality its attendant problems have plagued the world for a long time and the end of this social malaise seems not to be in sight. The female folk are usually commodified by society in varying degrees. Africa, being largely patriarchal in nature is worse off for this. The culture in most African societies have perpetrated and perpetuated this thorny issue. Language, which is an aspect of culture is often used to commodify, stereotype and disdain women. Frankly, language has not been fair enough to our women. An aspect of language used to innocuously spite or reduce the worth of women is proverbs. This study examined how some proverbs are used in Igbo ethnic in Nigeria to debase women. The paper revealed that Igbo people place high premium on proverbs, although there are many proverbs and sayings used in this part of the world to reduce women. The paper concluded that all proverbs that debase women should be discouraged and stopped.